Informasi Citra Anatomi pada Penggunaan Variasi Increment Pemeriksaan MSCT Abdomen Irisan Axial Kasus Nodul Hepar - Selfia Claudiana Rahma Dewi; Arinawati Arinawati; Darmini Darmini; Dimas Prakoso (Poltekkes Kemenkes Semarang, 2021)
Background : Liver nodules are tumors that are less than 2 cm in size and are single or multiple. In making a diagnosis of liver nodules can be done by examination of abdominal MSCT. According to Seeram (2009), using 50% overlapping there was an increase in nodule detection by 10% compared to incremental increments. The purpose of the study was to determine differences in information on anatomical images on the use of increment variations in abdominal MSCT examination and to find the appropriate increment values to produce optimal anatomical image information.Methods : This type of research is quantitative with an experimental approach. The study was conducted at the RSUD. Tugurejo Semarang, the image was taken from abdominal MSCT examination in 5 patients with a variation of increments of 100% (8 mm), 50% (4 mm), 30% (2, 4 mm). The results of the study were assessed by 3 respondents. Data analysis used the kappa statistical test, crosstabulation, and friedman.Results : From the statistical test, the results of the 2.4 mm increment value show clear anatomical criteria and can detect small nodules. Supported by using friedman statistical test p-value = 0.000 which means that p-value 0.05 thus Ha is accepted so that there are differences in anatomical image information.Conclusion : The most optimal increment value is 30% (2.4 mm) because it has the highest mean rank value of 2.37.